MENINGKATKAN HASIL BELAJAR IPA SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW KELAS IV SDN 660 MEKAR JAYA KABUPATEN LUWU - Nurasia; Sohriati, Eva; Sri Rahmadani, Uci; Khaerati (Universitas Cokroaminoto Palopo, 2023)
This study aims to improve students' science learning outcomes through the application of a jigsaw type cooperative learning model for class IV SDN 660 Mekar Jaya, Luwu Regency. This type of research is Classroom Action Research (PTK) which was carried out for 2 cycles. The subjects of this study were 24 students of grade IV SDN 660 Mekar Jaya, 11 male students and 14 female students. Collecting data in this study using observation, tests, and documentation. The research instrument consisted of learning implementation observation sheets and tests. The data analysis technique used is descriptive quantitative analysis. The results showed that there was an increase in student learning outcomes using the Jigsaw model in learning science for fourth grade students at SDN 660 Mekar Jaya. In cycle I, the average score of students' science learning outcomes was 60.4 (low category) and in cycle II, the average score of students' science learning outcomes was 77.6 (medium category).